Culex quinquefasciatus Late Trypsin Biosynthesis Is Translationally Regulated by Trypsin Modulating Oostatic Factor - Borovsky, Dov; Verhaert, Peter; Rougé, Pierre; Powell, Charles A.; De Loof, Arnold (Frontiers in Physiology, 2021)
Cx. quinquefasciatus late trypsin was purified by DEAE, affinity and C18 reverse-phase HPLC chromatography steps and the N-termina amino acid terminal sequence of the protein was determined after a final affinity chromatography. The late trypsin cDNA (855 bp) was cloned characterized and full sequence characterized. Three dimensional models of the pro-trypsin and activated trypsin were built and compared with other trypsin models. Trypsin Modulating Oostatic Factor (TMOF) concentrations in the hemolymph were determined by ELISA and compared with trypsin biosynthesis in the gut after the blood meal. Northern blot analyses of the trypsin transcripts during the blood meal indicate that the enzyme activity follows the increase and decrease of the trypsin transcript. Increase in TMOF concentrations circulating in the hemolymph reduced the amount of the trypsin synthesized in the mosquito gut . Injections of different amounts of TMOF (0.025 g to 50 g) affected the translation of the trypsin transcript without inhibiting its synthesis or degradation. Our conclusion is that the role of TMOF is to control the translation of trypsin biosynthesis in Cx. quinquefasciatus and probably also in other insects.